AN EFFORT IN CONTROLLING MYCOPLASMOSIS IN BROILER USING THE THIRD GENERATION OF QUINOLONE ANTIBIOTIC IN FIELD CONDITION - Darjono Darjono (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 1995)
A total of 2251 broilers treated with 20 mg/kg body weight enrofloxacin and 1947 broilers treated with 20 mg/kg body weight ofloxacin plus 2260 broilers treated whith 125 mg/kg body weight chlortetracyclin were allocated in an experiment lo evaluate the effectiveness of the third generation quinolone in controlling mykoplasmosis in field.Result of this experiment demonstrated that These group nf antibiotics could produced lower mortality altogether with the culling rate and higher market weight compared to those treated with chlortetracyclin (P < 0.0 1). Although, treatment of mycoplasmosis in field using antibiotics in this group did not completely eliminate the clinical signs and patological changes as compared to the experiments done in the laboratory. Economical evaluation indicated that usage of These groups of antibiotics for broilers was more beneficial than chlortetracyclin.